COVID-19-related deaths among women of reproductive age in Brazil: The burden of postpartum - Knobel, Roxana; Takemoto, Maíra L. S. [UNESP]; Nakamura-Pereira, Marcos; Menezes, Mariane O. [UNESP]; Borges, Vicente K.; Katz, Leila; Amorim, Melania M. R.; Andreucci, Carla B. (Wiley, 2021)
Objective: To compare risk of death due to COVID-19 among pregnant, postpartum, and non-pregnant women of reproductive age in Brazil, using the severe acute respiratory syndrome surveillance system (SARS-SS). Methods: A secondary analysis was performed of the Brazilian official SARS-SS, with data retrieved up to August 17, 2020. Cases were stratified by pregnancy status, risk factors or co-morbidities, and outcome (death or recovery). Multiple logistic regression was employed to examine associations between independent variables and risk of death. Results: A total of 24 805 cases were included, with 3129 deaths (12.6%), including 271 maternal deaths. Postpartum was associated with increased risk of death, admission to the intensive care unit (ICU), and mechanical ventilation. Co-morbidities with higher impact on case fatality rate among non-obstetric cases were cancer and neurological and kidney diseases. Among pregnant women, cancer, diabetes mellitus, obesity, and rheumatology diseases were associated with risk of death. In the postpartum subgroup, age over 35 years and diabetes mellitus were independently associated with higher chance of death. Conclusion: Postpartum was associated with worse outcomes among the obstetric population, despite lower risk of dying without accessing ICU care. Non-pregnant women with cancer, neurological diseases, and kidney diseases have a higher risk of death due to COVID-19.
Keywords: cardiovascular disease; COVID-19; maternal death; obesity; postpartum; pregnancy; women of reproductive age